Development of optical component for telecommunication use - Abdul Rahman, Rosly (Faculty of Science, 2008)
Optical components are essential in the present telecommunication and sensing systems since optical techniques are being used in almost all parts of the system. Future development in optical telecommunication and sensing requires new components and devices to be designed and constructed. Before these components and devices are to be installed they must be fully tested and improved to obtain the desired performance specifications. Therefore, this research aims at developing optical components for future telecommunication and sensing system. The focus would be on developing four basic optical components, namely fused fiber coupler, fiber Bragg grating (FBG), acousto optic devices and double-ball coupling module, with the aim of utilizing them in such systems. For the fused fiber coupler, the twist and pull method was utilized while the twisted portion of the fibers were heated using a stabilized oxygen flamed. Before this setup was implemented, the fusion splicing technique was studied and used to demonstrate the basic phenomenon of double fiber coupling. The simulation software (BPM) from Optiwave was applied earlier before experimental works in constructing the coupler was implemented. In the fabrication of FBG, the phase-mask technique was employed using an excimer laser and a beam alignment system. The excimer laser used the KrF gas mixture as the laser medium, giving light of 248 nm. The phase-mask holder was designed and constructed for use with a rectangular-shaped mask. Germanium doped fiber from Newport was employed in this fabrication. The cladding of the fiber portion that was to be written was removed before the fiber was exposed to the UV light of the excimer laser. The exposure time was carefully determined to ensure the desired reflectivity of the FBG was obtained. The simulation of the fabrication process was done using Opti-Grating software from Optiwave. An experimental setup for characterizing an acousto-optic modulator (AOM) was constructed and evaluated using a tunable HeNe laser with a precision rotating table. A beam profiling system was used in determining the position of the modulated output beam. A laser welding technique, utilizing a Nd:YAG laser and a precision motion control workstation, was employed in setting up a double-ball module for coupling light from a laser diode into a single mode fiber. A theoretical modelling of the module was concurrently developed to predict the possibility of using it for above coupling scheme. A series of fused fiber coupler with different coupling ratios were fabricated and tested. The 50/50, 40/60, 30/70, 20/80 and 10/90 couplers were successfully fabricated with a mean insertion loss of <1.0 dB. Theoretical and simulation works on the effect of flame instability indicate the requirement of a longer pulling and heating time for the correct fabrication of the couplers. The fabricated FBGs give reasonably high reflectivity of greater than 70%. Strain and temperature sensors were later made from these fabricated FBGs. Geometrical and temporal characteristics of the AOM were obtained and indicate the requirement of stabilized acoustic power for a good modulated output signal with minimum noise. A double-ball LD-fiber coupling module was successfully constructed and demonstrated a good coupling efficiency of 75% for high-divergent ratio LDs. For low-divergent ratio LDs, the single-ball LD-fiber coupling module was found to be more efficient. Both these results are predicted by the theoretical model developed. In general, the couplers and FBGs fabricated using the above techniques and the available machines were found to be capable of being used for future works in the setting up of devices for use in telecommunication and sensing. The AOM characterization system may also be used for future works with optical crystals that will be fabricated in the present facilities.